Biến tính hữu cơ clay montmorilonit K10 bằng hợp chất azo có chứa nhóm sunfonic axit - Xuân Hằng, Tô Thị; Trúc, Trịnh Anh; Vũ, Phạm Gia (Vietnam Journal of Chemistry, 2014)
Clay montmorillonite K10  was organically modified by cation exchange reaction with methyl orange.  The clay modified by methyl orange (K10DC) was characterized by infrared spectroscopy, X-ray diffraction, thermogravimetric analysis and scanning electronic microscopy. The epoxy coatings containing 2% clay K10DC was prepared and the dispersion degree of clay in coating was evaluated. Structure analysis by infrared spectroscopy  indicated that vibration bands at 1601 cm-1 and 1389 cm-1 characteristic of C-H bond in aromatic ring and C-N bond of methyl orange were also found in the spectra of clay K10DC. XRD analyze showed that the d001 spacing of clay-K10DC was 16.1 Å. These results indicate the intercalation of methyl orange molecules between silicate layers. Thermogravimetric analyze showed that the organic content in clay K10DC was 25,3 %. SEM observation demonstrated that in clay K10DC the silicate platelets are better separated then in pristine clay. XRD analyze results indicated that epoxy coating containing 2 % clay K10DC was intercalated nanocomposite.